Intensive Care - Shaikh, Nissar (IntechOpen, 2017)
The book Intensive Care is composed of ten chapters, which are the day-to-day practice diagnosis as well as rare disease and pediatric sepsis. It is written very well by the experts from the respective fields. We are sure and confident that this book will not only help the critical care physicians but also help acute care physicians, general practitioners, surgeons, and paramedical critical, intensive care, and acute care staff.